Status of Herd Health Biosecurity Measures and Associated Risk Factors in Dairy Farms in Asella–Bishoftu Milk Shed, Ethiopia - Yobsan Degefa Dadi; Fikru Gizaw Gurmessa; Minda Asfaw Geresu; Alemayehu Lemma; Teshita Edaso Beriso (Dairy, 2026)
Biosecurity measures (BSMs) are risk-reduction strategies that prevent pathogen introduction and limit disease spread in dairy herds. A cross-sectional questionnaire-based study was conducted from July 2025 to February 2026 to assess the BSM status and associated factors in dairy farms in Asella, Adama, and Bishoftu, Ethiopia. The towns were purposely selected, while the kebeles (the smallest administrative unit in Ethiopia) and the farms were randomly chosen. The data were collected from 300 farms using an online kobotoolbox. The external and internal biosecurity practice scores were calculated using the conceptual framework of Ghent University’s Biocheck tool. Overall, 85% of the farms had poor external BSMs (